THE SIGNIFICANCE OF USING THE EXPERIENCE OF THE OLDER GENERATION IN RAISING THE MORAL, EDUCATIONAL AND CULTURAL THINKING OF THE YOUTH (Scientific journal of the Fergana State University, 2024)
Today, the issues of transferring the experience of the moral succession of the older generation to the younger generation in every society, researching this process within the framework of social and humanitarian sciences, and rationally using its practical results justify the relevance of this research topic. It is evident that the participation of the representatives of the older generation in the development of industries and sectors is expanding in the composition of the world population. In particular, their activity in the spiritual-educational, educational process, their important role in the solution of social problems encountered during the renewal and changes in society is the basis for studying the activity of the older generation as an object of research. This, in turn, strengthens the need for research based on methodological approaches, the task of improving the mechanisms of effective use of the rich experience and scientific potential of the older generation in the formation of the moral culture of young people.